The GeoGebra software application in the perimeter concept formation in lower grades of elementary school - Milikić Milan P.; Maričić Sanja M.; Vulović Nenad R. (University of Kragujevac - Faculty of Pedagogy, Užice, 2022)
Numerous experimental studies have shown the advantages of using educational software in teaching mathematics. One of the dynamic educational software that has recently gained great popularity in teaching mathematics is GeoGebra. The geometric transformations and dynamic functions of the software can be effectively applied at various education levels, from elementary school to university level. The aim of this paper is to present, through selected examples, some possibilities of GeoGebra software that can help students in lower grades of elementary school become proficient in the concept of the perimeter of a figure in a plane (rectangle, square and triangle), thus allowing them to follow each step in the pattern formation for calculating the perimeter.